2018
DOI: 10.1016/j.acthis.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Follicle stimulating hormone receptor protein is expressed in ovine uterus during the estrous cycle and utero-placenta during early pregnancy: An immunohistochemical study

Abstract: Follicle stimulating hormone (FSH) is a well characterized gonadotropin that controls primarily development and functions of ovarian follicles in mammalian species. FSH binds to a specific G protein-coupled receptor (FSHR) belonging to the glycoprotein hormone receptor family that plays an essential role in reproduction. Although the primary location of FSHR is in the gonads (mainly in ovarian follicles), FSHR protein and/or mRNA have also been detected in extragonadal female reproductive tissues including emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies have shown that FSHR mRNA is expressed in GCs and oocytes from ovaries [37]. Moreover, the expression of FSHR mRNA in the different follicle and GC development stages varies significantly because of the different degrees of dependence on FSH [32,38]. Thus, in the process of mammalian ovarian follicle development the stimulation of FSH toward GCs needs to be combined with FSHR, and the amount of FSHR expressed on the surface of cells regulates the response of cells toward FSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that FSHR mRNA is expressed in GCs and oocytes from ovaries [37]. Moreover, the expression of FSHR mRNA in the different follicle and GC development stages varies significantly because of the different degrees of dependence on FSH [32,38]. Thus, in the process of mammalian ovarian follicle development the stimulation of FSH toward GCs needs to be combined with FSHR, and the amount of FSHR expressed on the surface of cells regulates the response of cells toward FSH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the mRNA levels of FSHR are dependent on the size of ovarian GCs [32]. Thus, we hypothesized that yak ovarian GC proliferation is due to differences in the expression level of FSHR because of BMP15 regulation.…”
Section: Knockdown Of Fshr Promotes Gc Proliferation In Yak Ovarianmentioning
confidence: 94%
“…The reproductive tract and uterine samples were collected on Day 20 of the estrous cycle, corresponding to proestrus and estrus phase of the cycle. Cross‐sections of uterine body and horn were dissected from middle part of uterus as described previously (Grazul‐Bilska et al, 2019; Grazul‐Bilska, Reyaz, et al, 2018). Briefly, as soon as transported to the laboratory, the samples and uterine regions were classified microscopically (LE, EG, DG, and ES).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have investigated the relationship between single nucleotide polymorphisms (SNPs) and gynecological diseases and aimed to elucidate the differences caused by FSH receptor isoforms. These studies have shown that SNPs may alter exogenous FSH levels, leading to differential responses to controlled ovarian hyperstimulation (COH) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%